E-Accessibility Policy for Social Inclusion of Persons with Disabilities in Tourism Marketing. Case Study from Regional Hotel Units in Greece - Halkiopoulos, Constantinos; Georgiadi, Maria; Gkintoni, Evgenia; Plexousakis, Stefanos (Technium Social Sciences Journal, 2020)
Nowadays, there is a growing interest for social inclusion and participation of persons with disabilities in tourist industry. Tourism is vital part of modern lifestyle and is considered beneficial for individuals with disabilities enhancing personal development and promoting quality of life. This project aims to investigate policies implemented and kind of services offered in tourist industry concerning persons with disabilities who have barriers for leisure time, not only physical but also internal, cultural and social. Research is being carried out on hotel units of four and five stars in Greece. Given the fact that tourism is considered as an important sector in the economy which improves the standard of living in a country, its adaptation to web tourism with innovations in technology and development of social policies appropriate for persons with disabilities, that can facilitate travelling, can promote tourist movement and also can offer a travel motive for them.